Why natural drugs being attracted to treat oral cancer? – Highlights from “Oral oncology reports” - Vinothini Gunasekaran; Palanivel Sathishkumar (Oral Oncology Reports)
Natural products derived from plants and microorganisms have been extensively studied for their anticancer potential, over half-century. Herein, the therapeutic efficacy, feasibility, and limitations of various natural drugs for the oral cancer treatment approaches published in “Oral Oncology Reports” from the past two years are discussed in detail. Overall, this study highlights that carotenoid (astaxanthin), alkaloids (piperine), polyphenols (epigallocatechin-3-gallate), flavanoids (genistein and quercetin), probiotic molecules (bacteriocin and extracellular polysaccharides), and marine peptides might be a promising natural drug for the treatment of oral cancer cells. Most of these natural drugs are highly biocompatible in nature. However, further study is needed in this field to bring this natural drug along with other combinations for real clinical trials to cure oral cancer.